2019
DOI: 10.3390/s19214692
|View full text |Cite
|
Sign up to set email alerts
|

A LAPS-Based Differential Sensor for Parallelized Metabolism Monitoring of Various Bacteria

Abstract: Monitoring the cellular metabolism of bacteria in (bio)fermentation processes is crucial to control and steer them, and to prevent undesired disturbances linked to metabolically inactive microorganisms. In this context, cell-based biosensors can play an important role to improve the quality and increase the yield of such processes. This work describes the simultaneous analysis of the metabolic behavior of three different types of bacteria by means of a differential light-addressable potentiometric sensor (LAPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…There is an urgent need for the design of sensitive, selective, and quick biosensors for the detection of bacteria in areas such as food analysis, health care, security, and environmental monitoring. Diseases related to pathogenic bacteria are a continuing major public health problem [155]. Latif et al reported the use of a MIP-based QCM biosensor for the detection of Escherichia coli (E. coli) bacteria and spores (Bacillus subtilis).…”
Section: Bacteriamentioning
confidence: 99%
“…There is an urgent need for the design of sensitive, selective, and quick biosensors for the detection of bacteria in areas such as food analysis, health care, security, and environmental monitoring. Diseases related to pathogenic bacteria are a continuing major public health problem [155]. Latif et al reported the use of a MIP-based QCM biosensor for the detection of Escherichia coli (E. coli) bacteria and spores (Bacillus subtilis).…”
Section: Bacteriamentioning
confidence: 99%
“…The pH-responsive ISFET-based sensors have been successfully used for noninvasively determining the growth, metabolism, and physiological conditions of cells and bacteria [47][48][49][50]. The acidification rate of the extracellular microenvironment is an important indicator of live cell state [15,51].…”
Section: Weak Acid/base-induced Ph Perturbation In a Cell Microenvironmentmentioning
confidence: 99%
“…Given the paramount importance of being able to assess the cellular metabolic activity during an in vitro experiment, several different approaches have been investigated and used during the past 40 years. In particular, metabolic activity can be indirectly measured by analysing parameters like oxygen uptake (due to cellular respiration) ( Wu et al, 2010 ; Kieninger et al, 2014 ), lactate production (due to anaerobic processes) and glucose consumption (during both aerobic and anaerobic conditions) ( Boero et al, 2011 ; Koman et al, 2015 ), and variations of the pH of the extracellular medium ( Baumann et al, 1999 ; Lorenzelli et al, 2003 ; Munoz-Berbel et al, 2013 ; McBeth et al, 2018 ; Sakata et al, 2018 ; Dantism et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%